PERBANDINGAN METODE EKSTRAKSI DNA PHENOL-CHLOROFORM DAN KIT EXTRACTION PADA SAPI ACEH DAN SAPI MADURA - Kamaliah Kamaliah (Universitas Islam Negeri Ar-Raniry, 2017)
DNA extract is the first phase of molecular research which really influences the quality of DNA isolate. The aim of this study was to find out the comparison of DNA extract by using Phenol-Chloroform and KIT extraction. The visualization of DNA isolate resulted from electrophoresis technique after leptin gen of Aceh’s cow and Madura’s cow were amplificated through in vitro (Polymerase Chain Reaction). There were not any techniques of DNA extraction which can provide excellence results as a whole. Phenol-Chloroform extraction method gives advantage for lower price, more sensitive in isolating DNA, and clear DNA ribbon. Meanwhile, KIT extraction method is easier, fast, and thick DNA produced.